Curable composition for temperature fuse and temperature fuse
Patent Information
- Application Number
- JP2023139473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0006】 本発明の温度ヒューズ用硬化性組成物を用いてなる温度ヒューズは、はんだリフロー温度である260℃では作動しないが350℃程度の比較的低温で作動することが可能であるという効果を奏する。
Smart Images

Figure 2025033629000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition for a thermal fuse and a thermal fuse. [Background technology]
[0002] Chip fuses, which use low-melting-point metals for wiring, are widely used to cut off circuits when an electronic board becomes abnormally hot. However, chip fuses are large in size, and conductive materials with fuse functions are desired. A known material with fuse functionality is thermal fuse ink, which uses carbon particles as conductive particles and forms an electrical conduction path by being printed and then baked (Patent Document 1). The carbon particles react with oxygen at an ambient temperature of 500°C or higher, burning and vaporizing, and the ink is activated. However, it has low conductivity, is difficult to activate on sealed electronic boards, and has a high activation temperature, posing safety issues. Also, a thermal fuse element is known that includes an adhesive layer containing an adhesive resin, thermally expandable resin particles, and conductive particles (Patent Documents 2 and 3). However, it is difficult to deform when there is a sealing such as solder resist on the top, and the operating temperature is lower than the solder reflow temperature generally used for electronic boards, so there are problems with mounting. In light of the above, there is a demand for a thermal fuse material that does not utilize material expansion and that can be easily activated at a relatively low temperature of around 350°C, but does not activate at the solder reflow temperature of 260°C, in order to be easily activated on electronic boards that are sealed with multi-layered layers or solder resist, etc. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6395315 [Patent Document 2] JP 2011-222773 A [Patent Document 3] JP 2008-269883 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a curable composition for a temperature fuse that provides a temperature fuse that does not operate at the solder reflow temperature of 260° C. but can operate at a relatively low temperature of about 350° C. The temperature fuse of the present invention operates when a crosslinked product of a polymer (A) having an alkoxysilyl group, contained in a cured product of the curable composition for a temperature fuse, shrinks due to thermal decomposition at a relatively low temperature of about 350° C., causing the conductive particles to follow and break the circuit. [Means for solving the problem]
[0005] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the present invention relates to a curable composition for a temperature fuse, comprising a polymer (A) having an alkoxysilyl group, conductive particles (B) and a thixotropy-imparting agent (C), in which the content of the polymer (A) having an alkoxysilyl group is 5 to 30% by weight, the content of the conductive particles (B) is 60 to 90% by weight, and the content of the thixotropy-imparting agent (C) is 0.05 to 10% by weight, based on the total weight of the polymer (A) having an alkoxysilyl group, the conductive particles (B) and the thixotropy-imparting agent (C). Effect of the Invention
[0006] A thermal fuse made using the curable composition for a thermal fuse of the present invention has the effect that it does not operate at the solder reflow temperature of 260°C, but can operate at a relatively low temperature of about 350°C. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram showing a thermal fuse according to an embodiment of the present invention, which is fabricated in a slit portion of a copper wiring. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The curable composition for a temperature fuse of the present invention contains a polymer (A) having an alkoxysilyl group, conductive particles (B) and a thixotropy-imparting agent (C).
[0009] The polymer (A) having an alkoxysilyl group is a polymer having a trialkoxysilyl group or a dialkoxysilyl group. Examples of the trialkoxysilyl group include a trimethoxysilyl group and a triethoxysilyl group. Examples of the dialkoxysilyl group include a methyldimethoxysilyl group and a methyldiethoxysilyl group. Of these alkoxysilyl groups, from the viewpoint of temperature responsiveness, a trialkoxysilyl group is preferred, and a trimethoxysilyl group and a triethoxysilyl group are more preferred.
[0010] From the viewpoints of stability at 260°C and temperature responsiveness of the shrinkage rate at 350°C, the polymer (A) having an alkoxysilyl group preferably has a thermal decomposition rate of 0 to 15 wt% / min at 260°C and preferably has a thermal decomposition rate of 15 to 30 wt% / min at 350°C. If the thermal decomposition rate at 260°C is 15% by weight / min or less, the circuit is less likely to break during the solder reflow process due to polymer shrinkage.Also, if the thermal decomposition rate at 350°C is 15-30% by weight / min, the conductive particles will follow the polymer shrinkage and break the circuit.
[0011] The thermal decomposition rate in the present invention was measured under the following conditions using a thermogravimetric differential thermal analyzer ("TG / DTA6200" manufactured by Seiko Instruments Inc.). <260℃ thermal decomposition rate> Approximately 10 mg of sample was heated in nitrogen from 30°C to 500°C at a rate of 10°C / min, and the TG curve obtained at 5°C before and after 260°C was analyzed to calculate the thermal decomposition rate from the weight change per minute based on the weight of the sample used in the measurement (measurement atmosphere: nitrogen at 200 ml / min, sample container: aluminum pan). <350℃ thermal decomposition rate> Approximately 10 mg of sample was heated in nitrogen from 30°C to 300°C at 60°C / min, and then heated in nitrogen from 300°C to 500°C at 10°C / min. The TG curve obtained was analyzed at 5°C before and after 350°C to calculate the thermal decomposition rate from the weight change per minute based on the weight of the sample used in the measurement (measurement atmosphere: nitrogen at 200 ml / min, sample container: aluminum pan).
[0012] As the polymer (A) having an alkoxysilyl group, a polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group, and a poly(meth)acrylate (A2) having an alkoxysilyl group are preferred. An example of the polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group is one obtained by reacting a polyether polyol having a polyalkylene oxide group with a monomer having an alkoxysilyl group.
[0013] Examples of polyether polyols having a polyalkylene oxide group include alkylene ether glycols such as diethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, and polytetramethylene glycol; alkylene ether triols such as polyoxyethylene trimethylolpropane, polyoxypropylene trimethylolpropane, polyoxyethylene glycerin, and polyoxypropylene glycerin; and alkylene ether tetraols such as polyoxyethylene pentaerythritol and polyoxypropylene pentaerythritol. From the viewpoint of temperature responsiveness, the polyalkylene oxide group is preferably a polyalkylene oxide group which is an alkylene having 2 to 4 carbon atoms, and more preferably a polyethylene oxide group, a polypropylene oxide group, or a polytetramethylene oxide group. Among these polyether polyols, from the viewpoint of temperature responsiveness, preferred are alkylene ether glycol and alkylene ether triol, and more preferred are polypropylene glycol and polyoxypropylene trimethylolpropane. The thermal decomposition rate can be controlled by adjusting the type and content of the alkylene oxide group. For example, increasing the content of the ethylene oxide group can decrease the thermal decomposition rate, whereas increasing the content of the propylene oxide group can increase the thermal decomposition rate.
[0014] Examples of monomers having an alkoxysilyl group include N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane. From the viewpoint of temperature responsiveness, the alkoxysilyl group is preferably an alkoxysilyl group having 1 to 3 carbon atoms, and more preferably a methoxysilyl group or an ethoxysilyl group. Of these monomers having an alkoxysilyl group, 3-isocyanatepropyltriethoxysilane is preferred from the viewpoint of temperature responsiveness.
[0015] The polymer (A1) having an alkoxysilyl group may be one obtained by directly reacting a polyether polyol having a polyalkylene oxide group with a monomer having an alkoxysilyl group, or may be one obtained by further reacting them using a binder such as an isocyanate.
[0016] The isocyanate is not particularly limited, and examples thereof include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,6-hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylene diisocyanate, and 1,6,11-undecane triisocyanate. Of these isocyanates, 1,6-hexamethylene diisocyanate is preferred from the viewpoint of temperature responsiveness.
[0017] The average number of alkoxysilyl groups per molecule of the polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group is preferably 1.5 to 3.0 from the viewpoint of temperature responsiveness. The average number of alkoxysilyl groups is calculated by comparing the peaks of the alkylene oxide group and the alkoxysilyl group by NMR measurement. That is, when measurement is performed using deuterated chloroform as the deuterated solvent, for example, the ratio of polypropylene groups to alkoxysilyl groups is calculated from the integrated value of the peak at 3.38 ppm derived from one proton of the methine group of propylene oxide when the polyalkylene oxide is propylene oxide, and the peak at 3.75 ppm derived from three protons of the methoxy group when the alkoxysilyl group is a methoxysilyl group, or the peak at 3.84 derived from two protons of the methylene group of the ethoxy group when the alkoxysilyl group is an ethoxysilyl group, and the weight average molecular weight measured by gel permeation chromatography (GPC) described below is calculated by approximating that the polymer consists of polypropylene and alkoxysilyl groups.
[0018] Examples of the poly(meth)acrylate (A2) having an alkoxysilyl group include poly(meth)acrylates containing a (meth)acrylate having an alkoxysilyl group as a constituent monomer. Examples of the (meth)acrylate having an alkoxysilyl group include γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, γ-(meth)acryloxypropylmethyldimethoxysilane, and γ-(meth)acryloxypropylmethyldiethoxysilane. From the viewpoint of temperature responsiveness, the alkoxysilyl group is preferably an alkoxysilyl group having 1 to 3 carbon atoms, and more preferably a methoxysilyl group or an ethoxysilyl group. Among these (meth)acrylates having an alkoxysilyl group, γ-(meth)acryloxypropyltrimethoxysilane is preferred from the viewpoint of temperature responsiveness.
[0019] Furthermore, the poly(meth)acrylate (A2) having an alkoxysilyl group may contain a monomer other than the (meth)acrylate having an alkoxysilyl group as a constituent monomer, such as an alkyl(meth)acrylate. Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tert-octyl (meth)acrylate, 2,3-dimethylhexyl (meth)acrylate, isoamyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, and stearyl. (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, 2-ethylhexyl diglycol (meth)acrylate, 4-butylphenyl (meth)acrylate, phenyl (meth)acrylate, and tetramethylphenyl (meth)acrylate. Of these alkyl (meth)acrylates, from the viewpoint of temperature responsiveness, methyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred. From the viewpoint of temperature responsiveness, the weight ratio of the alkyl (meth)acrylate contained in the poly(meth)acrylate (A2) having an alkoxysilyl group, that is, the weight ratio of the (meth)acrylate having an alkyl group with 1 to 6 carbon atoms to the (meth)acrylate having an alkyl group with 7 or more carbon atoms, is preferably 8:2 to 3:7, and particularly preferably 8:2 to 4:6. The thermal decomposition rate can be controlled by adjusting the type and content of alkyl (meth)acrylate. For example, increasing the content of methyl methacrylate can decrease the thermal decomposition rate.
[0020] From the viewpoint of temperature responsiveness, the average number of alkoxysilyl groups per molecule of the poly(meth)acrylate (A2) having alkoxysilyl groups is preferably 2 to 10. The average number of alkoxysilyl groups is calculated from the charging ratio of the constituent monomers and the weight average molecular weight measured by gel permeation chromatography (GPC).
[0021] From the viewpoint of temperature responsiveness, the weight average molecular weight of the polymer (A) having an alkoxysilyl group is preferably 2,000 to 50,000, the weight average molecular weight of (A1) is more preferably 10,000 to 50,000, and the weight average molecular weight of (A2) is more preferably 5,000 to 20,000. The weight average molecular weight of the polymer (A) having an alkoxysilyl group was measured using gel permeation chromatography (GPC) under the following conditions. Equipment: "HLC-8320GPC" [Tosoh Corporation] Columns: "TSKgel Guardcolumn SuperH-L" (1 column), "TSKgel SuperH4000", "TSKgel SuperH3000", "TSKgel SuperH2000" (3 columns) [all manufactured by Tosoh Corporation] Sample solution: 0.25% by weight tetrahydrofuran solution Solution injection volume: 10μl Flow rate: 0.6ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polystyrene Reference material: 11 standard polystyrenes (TSKstandardPOLYSTYRENE) (molecular weights: 292, 396, 500, 604, 708, 2630, 5970, 10200, 18100, 37900, 96400) [manufactured by Tosoh Corporation]
[0022] From the viewpoint of temperature responsiveness, the content of the polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group is preferably 20 to 80% by weight, more preferably 40 to 80% by weight, and particularly preferably 50 to 70% by weight, based on the weight of the polymer (A) having an alkoxysilyl group. From the viewpoint of temperature responsiveness, the content of the poly(meth)acrylate (A2) having an alkoxysilyl group is preferably 20 to 80% by weight, more preferably 20 to 60% by weight, and particularly preferably 30 to 50% by weight, based on the weight of the polymer (A) having an alkoxysilyl group.
[0023] Conductive particles (B) have an electrical conductivity of 10 6 There are no particular limitations as long as the particles have a volume resistivity of S / m or more, but silver particles and nickel particles are preferred from the viewpoint of volume resistivity. The volume average particle diameter of the conductive particles (B) is preferably 1 to 10 μm from the viewpoint of volume resistivity. Examples of the particle shape of the conductive particles (B) include flake particles (B1) and spherical particles (B2). From the viewpoint of temperature responsiveness, a mixture of flake particles (B1) and spherical particles (B2) is preferred. The mixing weight ratio [B1:B2] of (B1) and (B2) is preferably 2:1 to 1:1 from the viewpoint of temperature responsiveness. The volume average particle diameter of the conductive particles (B) is measured by dispersing the conductive particles (B) at 0.5% by weight in methyl ethyl ketone and using a laser diffraction particle size distribution analyzer "LA-750" (manufactured by HORIBA, Ltd.).
[0024] The thixotropy imparting agent (C) is not particularly limited as long as it is a particle other than the conductive particles (B), but from the viewpoint of heat resistance, silica is preferable. The specific surface area of the thixotropy imparting agent (C) is preferably 30 to 400 m from the viewpoint of temperature responsiveness. 2 / g. The specific surface area of the thixotropic agent (C) is measured by the BET method, and can be measured, for example, by a fully automatic specific surface area measuring device "Macsorb HM model-1200 series, manufactured by Mountec Co., Ltd.". When it is difficult to measure the specific surface area, the primary particle size can be used as a reference. The primary particle size is preferably 5 to 50 nm, and can be measured with a transmission electron microscope or a scanning electron microscope.
[0025] The content of the polymer (A) having an alkoxysilyl group is 5 to 30% by weight, preferably 10 to 30% by weight, and more preferably 15 to 30% by weight, based on the weight of (A), (B) and (C). If the content of (A) is less than 5% by weight, the temperature responsiveness of the conductivity is not exhibited, and if it exceeds 30% by weight, the heat resistance of the thermal fuse is not exhibited. The content of the conductive particles (B) is 60 to 90% by weight, preferably 69 to 90% by weight, and more preferably 75 to 90% by weight, based on the weight of (A), (B) and (C). If the content of (B) is less than 60% by weight, the thermal fuse will not exhibit heat resistance, and if it exceeds 90% by weight, the temperature response of the electrical conductivity will not be exhibited. The content of the thixotropy imparting agent (C) is 0.05 to 10% by weight, preferably 0.05 to 5% by weight, and more preferably 0.05 to 1% by weight, based on the weights of (A), (B), and (C) from the viewpoint of temperature responsiveness. If the content of (C) is less than 0.05% by weight, the thermal fuse will not exhibit heat resistance, and if it exceeds 10% by weight, the temperature responsiveness of the electrical conductivity will not be exhibited.
[0026] The curable composition for a temperature fuse of the present invention may contain a solvent in addition to the polymer (A) having an alkoxysilyl group, the conductive particles (B) and the thixotropy-imparting agent (C). Examples of the solvent include hydrocarbon solvents such as normal paraffin, aromatic solvents such as toluene, alcohol solvents such as isopropyl alcohol, and ketone solvents such as methyl ethyl ketone. Among these solvents, the hydrocarbon solvents are preferable from the viewpoint of preventing nozzle clogging due to drying during mounting.
[0027] When a solvent is added, the content of the solvent is preferably 1 to 20% by weight, more preferably 1 to 15% by weight, and particularly preferably 1 to 10% by weight, based on the weights of (A), (B), and (C), from the viewpoint of suppressing nozzle clogging due to drying during mounting.
[0028] The curable composition for a temperature fuse of the present invention may contain other components such as an antioxidant, a dehydrating agent, an adhesive, and a curing catalyst in addition to the polymer (A) having an alkoxysilyl group, the conductive particles (B), the thixotropy-imparting agent (C) and the solvent.
[0029] The antioxidant may be a hindered phenol antioxidant such as Irganox 245.
[0030] The dehydrating agent may be a silane coupling agent such as vinyltrimethoxysilane.
[0031] The adhesive may be a silane coupling agent having a polar group, such as 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
[0032] As the curing catalyst, titanate esters such as tetrabutyl titanate and tetrapropyl titanate, and organotin compounds such as dibutyltin dilaurate, dibutyltin maleate, dibutyltin diacetate, tin octoate, and tin naphthenate can be preferably used.
[0033] When other components are added, the total content of the other components is preferably 1 to 20% by weight, more preferably 1 to 15% by weight, and particularly preferably 1 to 10% by weight, based on the weight of (A), (B), and (C) from the viewpoint of temperature responsiveness.
[0034] The curable composition for a thermal fuse can be produced by mixing the polymer having an alkoxysilyl group (A), the conductive particles (B), the thixotropy imparting agent (C), and, if necessary, a solvent and other components, by a known method.
[0035] The thermal fuse of the present invention is a thermal fuse comprising a cured product of the curable composition for a thermal fuse, and the cured product contains a crosslinked product of the polymer (A) having an alkoxysilyl group. The molecular weight between crosslinking points of the crosslinked product obtained by crosslinking the alkoxysilyl group-containing polymer (A) is preferably 2,500 to 66,000, more preferably 2,500 to 27,000, and particularly preferably 2,500 to 22,000, from the viewpoints of heat resistance and temperature responsiveness. The molecular weight between crosslinks is calculated using the following formula (1) from classical rubber theory. Calculation formula (1) Molecular weight between crosslinking points=2(1+μ)ρRT / E' μ: Poisson's ratio (0.5) ρ: Density of the cured product (g / cm 3 ) R: Gas constant (8.314 J / K / mol) T: Absolute temperature (K) at which the plateau region of the storage modulus begins E': Storage modulus under tension (Pa)
[0036] <Density measurement of hardened product> The fuse curable composition is applied to a release PET sheet to a thickness of 0.5 mm, and then dried in a circulating air dryer at 90% relative humidity and 80°C for a specified time to crosslink (cure) the sheet-like cured product. The sheet-like cured product is peeled off from the release PET sheet and cut into a 2cm x 2cm square. The density is measured using an electronic specific gravity meter (SD-200L, manufactured by Alpha Mirage). The curing time for preparing the sample for density measurement is set to be the same as the curing time for the curable composition for fuses.
[0037] <Measurement of storage modulus> The fuse curable composition was applied to a thickness of 0.2 mm on a release PET sheet, and dried in a circulating air dryer at 90% humidity and 80°C for a specified time, crosslinked (cured), and produced a sheet-like cured product. The sheet-like cured product was peeled off from the release PET sheet and cut into 3.5cm x 0.5cm square pieces, and measured at 0.5Hz and a temperature range of -40 to 60°C at a heating rate of 4°C / min using a dynamic viscoelasticity measuring device (Rheogel E4000, manufactured by UBM Co., Ltd.) to measure the temperature T at which the plateau region of storage viscoelasticity begins and the storage modulus E' at that time. The curing time for preparing the sample for measuring the storage modulus is set to be the same as the curing time for the curable composition for fuses.
[0038] The molecular weight between crosslinking points of the crosslinked product of the polymer (A) can be adjusted by adjusting the average number of alkoxysilyl groups per molecule of the polymer (A) and the weight average molecular weight of the polymer. It can also be adjusted by adjusting the degree of the crosslinking reaction, i.e., the curing time (time of the crosslinking reaction).
[0039] A thermal fuse made of a cured product of the curable composition for a thermal fuse is thermally decomposed and contracted when heated, thereby cutting the circuit and operating. The heating temperature, i.e., the operating temperature, is preferably 300 to 450°C, more preferably 310 to 450°C, and particularly preferably 320 to 400°C, from the viewpoints of safety of electronic substrates and heat resistance to solder reflow.
[0040] A temperature fuse made of a cured product of the curable composition for a temperature fuse can be produced, for example, by heating the curable composition for a temperature fuse at a relative humidity of 25 to 100% and a temperature of 60 to 150°C for 0.1 to 5 hours to cure the curable composition for a temperature fuse. More specifically, the temperature fuse can be produced by crosslinking the polymer (A) having an alkoxysilyl group to obtain a crosslinked product of the polymer (A) having an alkoxysilyl group. When a solvent is contained, it can be removed by volatilizing it during production.
[0041] <Other> The present invention may include the following configurations. <1> A curable composition for a temperature fuse, comprising a polymer (A) having an alkoxysilyl group, conductive particles (B) and a thixotropy-imparting agent (C), wherein the content of the polymer (A) having an alkoxysilyl group is 5 to 30% by weight, the content of the conductive particles (B) is 60 to 90% by weight, and the content of the thixotropy-imparting agent (C) is 0.05 to 10% by weight, based on the total weight of the polymer (A) having an alkoxysilyl group, the conductive particles (B) and the thixotropy-imparting agent (C). <2> the polymer (A) having an alkoxysilyl group is a polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group and / or a poly(meth)acrylate (A2) having an alkoxysilyl group; <1> The curable composition for a thermal fuse according to claim 1. <3> The conductive particles (B) have a volume average particle size of 1 to 10 μm. <1> or <2> The curable composition for a thermal fuse according to claim 1. <4> The thixotropic agent (C) is silica. <1> ~ <3> 2. The curable composition for a thermal fuse according to claim 1 , <5> <1> ~ <4> 1. A temperature fuse comprising a cured product of the curable composition for a temperature fuse according to any one of claims 1 to 9, wherein the cured product contains a crosslinked product of the polymer (A) having an alkoxysilyl group, and the molecular weight between crosslinked points of the crosslinked product of the polymer (A) having an alkoxysilyl group is 2,500 to 66,000. EXAMPLES
[0042] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0043] Production Example 1 <Polymer (A1-1) Having a Polyalkylene Oxide Group and an Alkoxysilyl Group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 916.0 parts by weight of polypropylene glycol having a number average molecular weight of 2,000 [polypropylene glycol 2000 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)], 75.1 parts by weight of 1,6-hexamethylene diisocyanate [Desmodur H (manufactured by Sumika Covestro Urethane Co., Ltd.)] and 916 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, and then the mixture was reacted at 90 ° C. for 5 hours under stirring. Furthermore, 8.9 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, manufactured by Shin-Etsu Chemical Co., Ltd.) was reacted at 90 ° C. for 5 hours under stirring. The solvent was distilled off under reduced pressure at 100 ° C. to obtain a polymer (A1-1) having an alkoxysilyl group with a weight average molecular weight of 50,000 and an average number of triethoxysilyl groups per molecule of 1.8.
[0044] Production Example 2 <Polymer (A1-2) Having Polyalkylene Oxide Group and Alkoxysilyl Group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 7.2 parts by weight of polyoxypropylene trimethylolpropane having a number average molecular weight of 400 (SANNICS TP-400, manufactured by Sanyo Chemical Industries, Ltd.), 74.1 parts by weight of 1,6-hexamethylene diisocyanate [Desmodur H (manufactured by Sumika Covestro Urethane Co., Ltd.)] and 904 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, and then the mixture was reacted at 90°C for 3 hours with stirring. Furthermore, 903.6 parts by weight of polypropylene glycol having a number average molecular weight of 2,000 [polypropylene glycol 2000 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)] was reacted at 90°C for 5 hours with stirring. 15.1 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, manufactured by Shin-Etsu Chemical Co., Ltd.) was reacted at 90°C for 5 hours with stirring. The solvent was distilled off under reduced pressure at 100° C. to obtain a polymer (A1-2) having alkoxysilyl groups with a weight average molecular weight of 50,000 and an average number of triethoxysilyl groups per molecule of 3.0.
[0045] Production Example 3 <Polymer (A1-3) Having Polyalkylene Oxide Group and Alkoxysilyl Group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 890.0 parts by weight of polypropylene glycol having a number average molecular weight of 2,000 [polypropylene glycol 2000 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)], 66.0 parts by weight of 1,6-hexamethylene diisocyanate [Desmodur H (manufactured by Sumika Covestro Urethane Co., Ltd.)] and 900 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, and then the mixture was reacted at 90 ° C. for 5 hours under stirring. Furthermore, 44.0 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, manufactured by Shin-Etsu Chemical Co., Ltd.) was reacted at 90 ° C. for 5 hours under stirring. The solvent was distilled off at 100 ° C. under reduced pressure to obtain a polymer (A1-3) having an alkoxysilyl group with a weight average molecular weight of 10,000 and an average number of triethoxysilyl groups per molecule of 2.0.
[0046] Production Example 4 <Polymer (A1-4) Having Polyalkylene Oxide Group and Alkoxysilyl Group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 873.5 parts by weight of polypropylene glycol having a number average molecular weight of 2,000 [polypropylene glycol 2000 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)], 40.0 parts by weight of 1,6-hexamethylene diisocyanate [Desmodur H (manufactured by Sumika Covestro Urethane Co., Ltd.)] and 873 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, and then the mixture was reacted at 90°C for 5 hours under stirring. Furthermore, 86.5 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, manufactured by Shin-Etsu Chemical Co., Ltd.) was reacted at 90°C for 5 hours under stirring. The solvent was distilled off under reduced pressure at 100°C to obtain a polymer (A1-4) having an alkoxysilyl group with a weight average molecular weight of 5,000 and an average number of triethoxysilyl groups per molecule of 1.8.
[0047] Production Example 5 <Poly(meth)acrylate (A2-1) having an alkoxysilyl group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 556.0 parts by weight of methyl methacrylate, 323.0 parts by weight of 2-ethylhexyl methacrylate, 121.0 parts by weight of γ-methacryloxypropyltrimethoxysilane, and 2000 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, after which 10.1 parts by weight of azobisisobutyronitrile (AIBN) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added and reacted for 5 hours at 90° C. under stirring. The solvent was distilled off under reduced pressure at 100° C. to obtain poly(meth)acrylate (A2-1) having an alkoxysilyl group with a weight-average molecular weight of 20,000 and an average number of triethoxysilyl groups per molecule of 9.7.
[0048] Production Example 6 <Poly(meth)acrylate (A2-2) having an alkoxysilyl group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 550.0 parts by weight of methyl methacrylate, 420.0 parts by weight of 2-ethylhexyl methacrylate, 30.0 parts by weight of γ-methacryloxypropyltrimethoxysilane, and 2000 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, after which 10 parts by weight of AIBN was added and reacted for 5 hours under stirring at 90° C. The solvent was distilled off under reduced pressure at 100° C. to obtain poly(meth)acrylate (A2-2) having an alkoxysilyl group with a weight-average molecular weight of 20,000 and an average number of triethoxysilyl groups per molecule of 2.4.
[0049] Production Example 7 <Poly(meth)acrylate (A2-3) having an alkoxysilyl group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 540.0 parts by weight of methyl methacrylate, 270.0 parts by weight of 2-ethylhexyl methacrylate, 190.0 parts by weight of γ-methacryloxypropyltrimethoxysilane, and 2000 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, after which 40 parts by weight of azobisisobutyronitrile (AIBN) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added and reacted for 5 hours at 90° C. under stirring. The solvent was distilled off under reduced pressure at 100° C. to obtain poly(meth)acrylate (A2-3) having an alkoxysilyl group with a weight-average molecular weight of 5,000 and an average number of triethoxysilyl groups per molecule of 3.8.
[0050] Production Example 8 <Poly(meth)acrylate (A2-4) having an alkoxysilyl group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 550.0 parts by weight of methyl methacrylate, 200.0 parts by weight of 2-ethylhexyl methacrylate, 250.0 parts by weight of γ-methacryloxypropyltrimethoxysilane, and 2000 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, after which 100 parts by weight of AIBN was added and reacted for 5 hours at 90° C. under stirring. The solvent was distilled off under reduced pressure at 100° C. to obtain poly(meth)acrylate (A2-4) having an alkoxysilyl group with a weight-average molecular weight of 2,000 and an average number of triethoxysilyl groups per molecule of 2.0.
[0051] Production Example 9 <Poly(meth)acrylate (A2-5) having an alkoxysilyl group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 550.0 parts by weight of methyl methacrylate, 440.4 parts by weight of 2-ethylhexyl methacrylate, 9.6 parts by weight of γ-methacryloxypropyltrimethoxysilane, and 2000 parts by weight of toluene were charged, and the inside of the reaction vessel was replaced with nitrogen gas, after which 2 parts by weight of AIBN was added and reacted for 5 hours under stirring at 90° C. The solvent was distilled off under reduced pressure at 100° C. to obtain poly(meth)acrylate (A2-5) having an alkoxysilyl group with a weight-average molecular weight of 50,000 and an average number of triethoxysilyl groups per molecule of 1.9.
[0052] Production Example 10 <Polymer (A1-5) Having Polyalkylene Oxide Group and Alkoxysilyl Group> A pressure-resistant reaction vessel equipped with a thermometer and a stirrer was charged with 910.0 parts by weight of polypropylene glycol [polypropylene glycol 5000 (Qingdao Fengtong Technology Trading Co., Ltd.)] having a number average molecular weight of 4,500, and 90.0 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, Shin-Etsu Chemical Co., Ltd.), and the atmosphere in the reaction vessel was replaced with nitrogen gas, and the mixture was reacted for 5 hours at 90°C with stirring. A polymer (A1-5) having a weight average molecular weight of 5,000 and an alkoxysilyl group with an average number of triethoxysilyl groups per molecule of 1.8 was obtained.
[0053] Production Example 11 <Polymer (A1-6) Having Polyalkylene Oxide Group and Alkoxysilyl Group> In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 48 parts by weight of polyoxypropylene trimethylolpropane (Sannyx TP-400, manufactured by Sanyo Chemical Industries, Ltd.) having a number average molecular weight of 400 and 0.05 parts by weight of potassium hydroxide were added, and the mixture was replaced with nitrogen, and then dehydration was performed at 120°C under reduced pressure (2.7 x 103 Pa) for 1 hour. Next, 5952 parts by weight of propylene oxide (manufactured by Tokyo Chemical Industry Co., Ltd.) was introduced at 150°C so that the gauge pressure was 0.01 to 0.03 MPa. 6 parts of "Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.)" were added to the reaction product, and the catalyst was adsorbed at 90°C, followed by filtration to obtain polyether (polyoxypropylene trimethylolpropane 49200). The number average molecular weight of the polyether was 49,200. In a pressure-resistant reaction vessel equipped with a thermometer and a stirrer, 985.4 parts by weight of the obtained polyether and 14.6 parts by weight of 3-isocyanatepropyltriethoxysilane (KBE-9007N, Shin-Etsu Chemical Co., Ltd.) were charged, and after replacing the atmosphere in the reaction vessel with nitrogen gas, the mixture was reacted for 5 hours with stirring at 90° C. A polymer (A1-6) having an alkoxysilyl group with a weight-average molecular weight of 50,000 and an average number of triethoxysilyl groups per molecule of 3.0 was obtained.
[0054] [Table 1]
[0055] Examples 1 to 20, Comparative Examples 1 to 4 A polymer having an alkoxysilyl group (A), an antioxidant, a diluent, a dehydrating agent and an adhesion promoter were mixed in the proportions shown in Tables 2 and 3, and then the conductive particles (B) and a thixotropy promoter (C) were added and mixed. After that, a curing catalyst was further added and mixed to obtain a paste-like curable composition for a thermal fuse. A copper-clad laminate (R-1705, Panasonic Corporation) with a thickness of 70 μm is spin-coated with a resist (OFPR-800, Tokyo Ohka Kogyo Co., Ltd.) at 1000 rpm and pre-baked at 90 ° C for 90 seconds. After that, a pattern is formed through a mask, and the exposed part is removed with a developer (NMD-W (Tokyo Ohka Kogyo Co., Ltd., TMAH-2.38 wt% aqueous solution)). A wiring pattern with a width of 3 mm and a length of 20 mm is drawn by post-baking at 120 ° C for 5 minutes, and a copper wiring is produced by etching with an etching solution (2.0 mol / L iron (III) chloride aqueous solution) at 50 ° C for 20 minutes. A cut line is made in the center of the copper wiring length direction with a cutter with a thickness of 100 μm, and a 200 μm slit is produced by etching with the etching solution at 25 ° C for 30 minutes. The prepared wiring was immersed in a resist remover (a mixture of 30 weight % monoethanolamine (Tokyo Chemical Industry Co., Ltd.), 10 weight % sulfolane (Tokyo Chemical Industry Co., Ltd.), and 60 weight % diethylene glycol monobutyl ether (Tokyo Chemical Industry Co., Ltd.)) at room temperature for 1 hour to remove the resist, and then a curable composition for a temperature fuse was applied to the slit portion and cured at 80°C and 90% relative humidity for 2 hours to prepare a temperature fuse in the slit portion of the copper wiring (Figure 1).
[0056] Raw materials listed in Tables 2 and 3 Conductive particles (B1-1): Silcoat AgC-271B, manufactured by Fukuda Metal Foil and Powder Co., Ltd. (flake-shaped particles with a volume average particle size of 1.3 μm) Conductive particles (B1-2): Silcoat AgC-224, manufactured by Fukuda Metal Foil and Powder Co., Ltd. (flake-shaped particles with a volume average particle size of 9.5 μm) Conductive particles (B2-1): Silcoat AgC-161T, manufactured by Fukuda Metal Foil and Powder Co., Ltd. (spherical particles with a volume average particle size of 1.3 μm) Conductive particles (B2-2): Ag-HWQ 10 μm, manufactured by Fukuda Metal Foil and Powder Co., Ltd. (spherical particles with a volume average particle size of 10 μm) Thixotropic agent (C-1): Aerosil R812S, manufactured by Nippon Aerosil Co., Ltd. (specific surface area 300 m 2 / g) Thixotropic agent (C-2): Aerosil OX50, manufactured by Nippon Aerosil Co., Ltd. (specific surface area 50 m 2 / g) Antioxidant: Irganox 245, manufactured by BASF Japan Ltd. Dehydrating agent: Vinyltrimethoxysilane, KBM-1003, manufactured by Shin-Etsu Chemical Co., Ltd. Adhesive: 3-aminopropyltrimethoxysilane, KBM-903, manufactured by Shin-Etsu Chemical Co., Ltd. Curing catalyst: Dioctyltin diversatate, Neostan U-830, manufactured by Nitto Kasei Co., Ltd. Solvent: Normal paraffin N-11, manufactured by ENEOS Corporation
[0057] <Heat resistance of thermal fuses> The copper wiring having each of the produced thermal fuses was heated at 260° C. for 1 hour, and the resistance values at both ends of the thermal fuse after heating were measured using a tester "LCR HiTESTER 3532-50, manufactured by Hioki E.E. Corporation." [Evaluation Criteria] 〇: Resistance value less than 0.5Ω △: Resistance value is 0.5Ω or more and less than 5Ω ×: Resistance value 5Ω or more
[0058] <Temperature response of electrical conductivity> The copper wiring with each thermal fuse produced was heated at 260°C for 10 seconds, and the resistance value at both ends of the thermal fuse after heating was measured using a tester "LCR HiTESTER 3532-50, manufactured by Hioki E.E. Corporation." It was determined that the fuse had responded (activated) when the resistance value reached 1,000Ω or more. If the fuse did not activate, the heating temperature was further increased in 10°C increments up to a maximum of 450°C, and the same procedure was repeated. The lowest temperature at which the fuse activated (activation temperature) was evaluated according to the following criteria. In addition, if the fuse activated at 320-400°C, a new thermal fuse was produced and evaluated for whether it would activate even if heated for 5 seconds at the activated temperature. [Evaluation Criteria] ◎: Activated when heated to 320-400℃ for 5 seconds ○: Operated at 320~400℃ △: Operated at 300~310℃ or 410~450℃ ×: Operated at 290℃ or below, or did not operate at 450℃
[0059] [Table 2]
[0060] [Table 3] [Industrial Applicability]
[0061] A thermal fuse made of the cured product of the curable composition for a thermal fuse of the present invention does not activate at the solder reflow temperature of 260°C, but can activate at a relatively low temperature of around 350°C, and is suitable for use in printed circuit boards and electronic circuit boards on which active elements and / or passive elements are soldered, and in semiconductor devices or module units on which semiconductor elements including transistors and diodes are mounted.
Claims
1. The curable composition for a temperature fuse contains a polymer (A) having an alkoxysilyl group, conductive particles (B) and a thixotropy-imparting agent (C), wherein the content of the polymer (A) having an alkoxysilyl group is 5 to 30% by weight, the content of the conductive particles (B) is 60 to 90% by weight, and the content of the thixotropy-imparting agent (C) is 0.05 to 10% by weight, based on the total weight of the polymer (A) having an alkoxysilyl group, the conductive particles (B) and the thixotropy-imparting agent (C).
2. 2. The curable composition for a temperature fuse according to claim 1, wherein the polymer (A) having an alkoxysilyl group is a polymer (A1) having a polyalkylene oxide group and an alkoxysilyl group and / or a poly(meth)acrylate (A2) having an alkoxysilyl group.
3. 2. The curable composition for a temperature fuse according to claim 1, wherein the conductive particles (B) have a volume average particle size of 1 to 10 μm.
4. 2. The curable composition for a thermal fuse according to claim 1, wherein the thixotropic agent (C) is silica.
5. A temperature fuse comprising a cured product of the curable composition for a temperature fuse according to any one of claims 1 to 4, wherein the cured product includes a crosslinked product of the polymer (A) having an alkoxysilyl group, and the molecular weight between crosslinking points of the crosslinked product of the polymer (A) having an alkoxysilyl group is 2,500 to 66,000.
Citation Information
Patent Citations
Magnetic position detector
JP1988095315A
Fuse function element, its manufacturing method, circuit board using fuse function element, and its manufacturing method
JP2008269883A
Polymer temperature fuse element, temperature sensor, and battery pack
JP2011222773A